Ichthyofauna of the ribeirão sucuri, a tributary of the rio tietê, upper rio paraná basin, southeastern Brazil - Reia, Lais [UNESP]; Silva, Gabriel S. Costa E. [UNESP]; Garcia-Ayala, James R. [UNESP]; Vicensotto, Ana Maria P. F. [UNESP]; Benine, Ricardo C. [UNESP] (Pensoft Publishers, 2020)
The ribeirão Sucuri, a tributary of the rio Tietê, and part of the upper rio Paraná basin, is located in the municipality of Pongaí, São Paulo state. The ichthyofauna of ribeirão Sucuri was sampled at nine collection sites in May 2018. Our study captured 408 specimens representing five orders, 11 families, and 35 species. Among the species collected, two have not been previously reported from the rio Tietê basin: Eigenmannia guairaca Peixoto, Dutra & Wosiacki, 2015 and Hoplias misionera Rosso, Mabragaña, González-Castro, Delpiani, Avigliano, Schenone & Días de Astarloa, 2016. Additionally, four species were found that are non-native: Hoplias misionera, Poecilia reticulata Peters, 1859, Roeboides descalvadensis Fowler, 1932, and Satanoperca sp. This study represents the first fish inventory of a tributary on the left margin of the Tietê-Batalha sub-basin and only the second for this portion of the rio Tietê. Our results increase to 55 the number of species recorded from this sub-basin and add data on the putative morphological variation in several species.
Keywords: Diversity; Inventory; Neotropical freshwater fishes; Tietê-Batalha sub-basin